‫إدارة‬‫مخاطر‬ ‫الصرف‬ ‫وانعكاساتها‬ ‫على‬ ‫الأداء‬ ‫المالي‬ ‫دراسة‬‫مقارنة‬ ‫بين‬ ‫وكالة‬ ‫البنك‬ ‫الخارجي‬ ‫الجزائري‬ ‫و‬ ‫وكالة‬‫بنك‬ ‫الخليج‬ ‫الجزائري‬ - ‫ــنوال‬ ‫زوي‬‫ـ‫ــتة‬; خول‫ــة ‫راف‬‫ــع‬ ‫‬ (My University, 2018)
Banks face exchange rate risk, which is considered one of the most common risks. more dangerous in banks, so we tried through this study in order to determine the bank's ability to manage this type of risk by following a set of different strategies to hedge currency risk, which also reflects on the financial performance of banks and thus achieve the objectives of the rule. To achieve this, a field study was carried out in the foreign bank of Algeria and the bank of the Gulf of Algeria, we relied on the descriptive approach in the theoretical part, and the comparative approach in the practical part is through a questionnaire sent to both banks, then the data was analyzed using SPSS program. Finally, the study concluded that good management of foreign exchange risks is reflects positively on the financial performance of banks. ........................................................ تواجه البنوك مخاطر أسعار الصرف، والتي تعتبر من أكثر المخاطر شيوعا. أكثر خطورة في البنوك، لذلك حاولنا من خلال هذه الدراسة أن وتحديد قدرة البنك على إدارة هذا النوع من المخاطر من خلال اتباع أ مجموعة من الاستراتيجيات المختلفة للتحوط من مخاطر العملة، وهو ما يعكس أيضًا على الأداء المالي للمصارف وبالتالي تحقيق أهداف القاعدة. ولتحقيق ذلك تم إجراء دراسة ميدانية في بنك الجزائر الخارجي وبنك الجزائر على ضفة خليج الجزائر اعتمدنا على المنهج الوصفي في البحث الجزء النظري، أما المنهج المقارن في الجزء العملي فهو من خلال أ تم إرسال الاستبيان إلى كلا البنكين، ومن ثم تم تحليل البيانات باستخدام برنامج SPSS . وأخيرا، خلصت الدراسة إلى أن الإدارة الجيدة لمخاطر الصرف الأجنبي هي وينعكس إيجاباً على الأداء المالي للبنوك.